Beta-diversity in temperate and tropical forests reflects dissimilar mechanisms of community assembly - Myers, Jonathan A.; Chase, Jonathan M.; Jiménez, Iván; Jørgensen, Peter M.; Araujo-Murakami, Alejandro; Paniagua-Zambrana, Narel; Seidel, Renate (Ecology letters, 2013)
Site‐to‐site variation in species composition (β‐diversity) generally increases from low‐ to high‐diversity regions. Although biogeographical differences in community assembly mechanisms may explain this pattern, random sampling effects can create this pattern through differences in regional species pools. Here, we compared assembly mechanisms between spatially extensive networks of temperate and tropical forest plots with highly divergent species pools (46 vs. 607 species). After controlling for sampling effects, β‐diversity of woody plants was similar and higher than expected by chance in both forests, reflecting strong intraspecific aggregation. However, different mechanisms appeared to explain aggregation in the two forests. In the temperate forest, aggregation reflected stronger environmental correlations, suggesting an important role for species‐sorting (e.g. environmental filtering) processes, whereas in the tropics, aggregation reflected stronger spatial correlations, more likely reflecting dispersal limitation. We suggest that biogeographical differences in the relative importance of different community assembly mechanisms contribute to these striking gradients in global biodiversity.